Hidden regret in insurance markets: Adverse and advantageous selection - Rachel J. Huang; Alexander Muermann; Larry Y. Tzeng (Goethe University Frankfurt, Center for Financial Studies (CFS), 2008)
We examine insurance markets with two types of customers: those who regret suboptimal decisions and those who don.t. In this setting, we characterize the equilibria under hidden information about the type of customers and hidden action. We show that both pooling and separating equilibria can exist. Furthermore, there exist separating equilibria that predict a positive correlation between the amount of insurance coverage and risk type, as in the standard economic models of adverse selection, but there also exist separating equilibria that predict a negative correlation between the amount of insurance coverage and risk type, i.e. advantageous selection. Since optimal choice of regretful customers depends on foregone alternatives, any equilibrium includes a contract which is oþered but not purchased.
urn:nbn:de:hebis:30-60654
Keywords: D03; D81; D82; 330; Asymmetric Information; Regret; Insurance; Versicherungsmarkt; Asymmetrische Information; Adverse Selection; Versicherungsökonomik; Entscheidung bei Risiko; Theorie